Empowerment Strategy Of Traditional Fishermen Community Towards Improving Household Economic Welfare In Nagari Painan Selatan, IV Jurai District, Pesisir Selatan Regency - Yudhiatma, Rovel; Zusmelia, Zusmelia; Irwan, Irwan (International Journal of Educational Research Excellence, 2026)
Study This aim For analyze existing programs implemented by the government village and government area through service maritime and fisheries that have not been capable increase welfare economy House ladder fisherman traditional in Nagari Painan Selatan, IV Jurai District, Jurai Regency South Coast, and analyze form of empowerment strategy public fisherman traditional For improvement to welfare economy House stairs in Nagari Painan Selatan, IV Jurai District, Jurai Regency South Coast. Research This use the theory of community empowerment strategy put forward by Mardikanto and Subianto (2019), the theory evaluation empowerment society proposed by Daniel Stufflebeam (2007) and theory welfare economics proposed by Amartya Kumar Sen. Research This use post-positivistic paradigm with mixed method approach. Withdrawal informant done with purposive sampling qualitative and technical election respondents use thinking Arikunto 2010. Unit of analysis study This is at individuals and homes stairs. Initial data collection techniques with studies documents, distribution questionnaire, interview in-depth, observation participants, and FGD. Procedure data processing qualitative use thinking Milles Huberman and quantitative using AHP and SWOT. Research results This show that the program implemented by the government Not yet increase welfare economy House ladder due to capacity source Power man Not yet own skills, access to capital and markets still limited, program implementation in post- program mentoring and monitoring is not optimal, and program implementation is not yet fulfil need fishermen. The empowerment strategy community that is carried out that is do strengthening capacity and skills fishermen, giving access capitalization to fishermen, strengthening institutional fishermen and groups fishermen, and strengthening development business productive fisherman.